Facilitated subcutaneous immunoglobulin (fSCIg) therapy – practical considerations. (22nd September 2015) - Ponsford, M; Carne, E; Kingdon, C; Joyce, C; Price, C; Williams, C; El-Shanawany, T; Williams, P; Jolles, S
Summary: There is an increasing range of therapeutic options for primary antibody-deficient patients who require replacement immunoglobulin. These include intravenous immunoglobulin (IVIg), subcutaneous immunoglobulin (SCIg), rapid push SCIg and most recently recombinant human hyaluronidase-facilitated SCIg (fSCIg). Advantages of fSCIg include fewer needle punctures, longer infusion intervals and an improved adverse effect profile relative to IVIg. Limited real-life experience exists concerning the practical aspects of switching or starting patients on fSCIg. We describe the first 14 patients who have been treated with fSCIg at the Immunodeficiency Centre for Wales (ICW), representing more than 6 patient-years of experience. The regimen was well tolerated, with high levels of satisfaction and no increase in training requirement, including for a treatment-naive patient. Two patients discontinued fSCIg due to pain and swelling at the infusion site, and one paused therapy following post-infusion migraines. Ultrasound imaging of paired conventional and facilitated SCIg demonstrated clear differences in subcutaneous space distribution associated with a 10-fold increase in rate and volume delivery with fSCIg. Patient profiles for those choosing fSCIg fell into two main categories: those experiencing clinical problems with their current treatment and those seeking greater convenience and flexibility. When introducing fSCIg, consideration of the type and programming of infusion pump, needle gauge and length, infusion site, up-dosing schedule, home training and patient information are important, as these may differ from conventional SCIg. This paper provides guidance on practical aspects of the administration, training and outcomes to help inform decision-making for this new treatment modality.